Ectopic Adrenocorticotropic Hormone–Secreting Pituitary Adenomas: An Underestimated Entity. Issue 4 (19th January 2017) - Knappe, Ulrich J.; Jaspers, Christian; Buschsieweke, Desirée; Reinbold, Wolf-Dieter; Alomari, Ali; Saeger, Wolfgang; Ehlenz, Klaus; Mann, W. Alexander; Kann, Peter Herbert; Feldkamp, Joachim
Abstract: BACKGROUND: The diagnosis of Cushing disease is based on endocrinological pa-rameters, with no single test being specific. In some patients, dynamic thin-slice sellar magnetic resonance imaging fails to detect a pituitary tumor. OBJECTIVE: The purpose of this study is to investigate the role of ectopic pituitary adenoma in this situation. METHODS: In a retrospective chart review, 5 patients (6%) with ectopic adenomas were identified in 83 consecutive patients undergoing transsphenoidal surgery for adrenocorticotropic hormone (ACTH)-secreting pituitary adenomas by 1 surgeon. RESULTS: In all 5 patients (all female, 32-41 years of age), an exclusively extrasellar ACTH-secreting adenoma was excised. Three adenomas were located in the cavernous sinus, 1 in the sphenoid sinus, and 1 in the ethmoidal cells. Histologically, none of the tumors showed signs of aggressiveness. Three of the 5 adenomas specifically expressed somatostatin receptor 5. In 4 patients with Cushing disease, postoperative remission was obtained, with 1 recurrence after 14 months. In the patient with Nelson syndrome, ACTH decreased from >800 to <80 pg/mL. Three patients underwent previous surgery elsewhere, including 1 hypophysectomy. In this case, the ectopic adenoma (positive for somatostatin receptor 5) in the ethmoidal cells turned out to be positive on gallium 68 DOTATATE positron emission tomography/computed tomography. CONCLUSION: The incidence of primarily ectopic ACTH-secreting adenomas in this series was 6%. In cases of negative MRI findings, an ectopic ACTH-secreting adenoma should be taken into account. 68 Ga DOTATATE positron emission tomography/computed tomography may identify ectopic pituitary adenomas. Hypophysectomy should always be avoided in primary surgery for CD.